2014
DOI: 10.1007/s13239-014-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Blood Flow Simulations by Incorporating Measured Subject-Specific Wall Motion

Abstract: Phone: +4613282335, email: Jonas.Lantz@liu.se, fax: +4613281101 2 Abstract Purpose: Physiologically relevant simulations of blood flow require models that allow for wall deformation.Normally a fluid-structure interaction (FSI) approach is used; however, this method relies on several assumptions and patient-specific material parameters that are difficult or impossible to measure in vivo. Method:In order to circumvent the assumptions inherent in FSI models, aortic wall motion was measured with MRI and prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The Swedish National Infrastructure for Computing (SNIC) is acknowledged for computational resources provided by the National Supercomputer Centre (Grant No. SNIC2014- [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The Swedish National Infrastructure for Computing (SNIC) is acknowledged for computational resources provided by the National Supercomputer Centre (Grant No. SNIC2014- [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Also included are the mass wave reflections from the arterial branches, the pulsatile movement of the heart, the residual stress, and the grade of fixation of the wall. 5 , 6 Finally, the knowledge of the embryologic origin of the anatomical variations of the aortic arch is a very important issue in order to understand the pathophysiology of the aortic dissection. 7 – 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in healthy aortae have shown that inclusion of the motion of the vessel wall alters the WSS values (Lantz et al, 2014;Reymond et al, 2013). However, it is not clear how much WSS will be affected by the wall motion in simulations of AD, wherein vessel wall distensibility is reduced (Ganten et al, 2009).…”
Section: Resultsmentioning
confidence: 99%